الاستثمار في عملة البتكوين - Rachmat Murdani Mursal (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
ABSTRACT Rachmat Murdani Mursal: